USE OF SOLID RECOVERED FUEL (SRF) IN CEMENT INDUSTRY – ECONOMIC AND ENVIRONMENTAL IMPLICATIONS - Spasojević-Brkić, Vesna K; Dondur, Nikola; Jovović, Aleksandar; Radić, Dejan; Obradović, Marko; Todorović, Dušan; Josipović, Sonja; Stanojević, Miroslav (Journal of Applied Engineering Science, 2015)
In the paper we have analysed whether and to what extent co-incineration of secondary fuels in cement manufacturing is cost-effective. Techno-economic assessment shows that combined combustion of solid recovered fuel and traditional fossil fuel (petroleum coke) is economically viable to the extent of 20:80 per cent. The paper also concluded that the impact of the plants on the quality of air would be negligible.